Micropropagação do Imbiruçu (Pseudobombax simplicifolium A. Robyns) e da Baraúna (Schinopsis brasiliensis Engl.) e uso dos fluorocromos CMA3/DAPI na caracterização citogenética do Imbiruçu - Valeriano, Jessica Coelho (2016)
Schinopsis brasiliensis Engl. and Pseudobombax simplicifolium A. Robins are species widely distributed in the Brazilian semiarid. The pressure on the genetic resources from Caatinga biome, mainly medicinal and for wood, caused by subsistence or commercial use, leads to reduce genetic variability of these species. Based on that, the cytogenetic and the tissue culture can support the characterization and propagation strategies of their populations. The research goals of this study were evaluate growth regulators and culture media effects on the establishment and in vitro micropropagation for the species, and the use of fluorochromes CMA3/DAPI in the cytogenetic characterization of P. simplicifolium. For P. simplicifolium it was evaluated different DKW ingredient concentration, added or not activated charcoal and different concentration of BAP and IBA on the establishment and in vitro multiplication of the species. For S. brasiliensis, it was evaluated the micropropagation media DKW and WPM (with different concentration of BAP and IBA) and the use of activated charcoal and polyvinylpyrrolidone to reduce the oxidation during establishment of in vitro cultivation of the species. In S. brasiliensis, the addition of BAP in the micropropagation media did not promote in vitro multiplication of the species. In P. simplicifolium, the results obtained for variables studied varied depending on the regulators concentrations and among genotypes. Concentrations above 4.92 and 6.64 μM.L-1 AIB inhibited the multiplication in vitro in both species. The double staining CMA3/DAPI allowed the visualization of 2n = 84 chromosomes and different numbers of CMA+ blocks in the genotypes of P. simplicifolium.